6(5x+4)+3(2x+6)+5=36x+48

Simple and best practice solution for 6(5x+4)+3(2x+6)+5=36x+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5x+4)+3(2x+6)+5=36x+48 equation:


Simplifying
6(5x + 4) + 3(2x + 6) + 5 = 36x + 48

Reorder the terms:
6(4 + 5x) + 3(2x + 6) + 5 = 36x + 48
(4 * 6 + 5x * 6) + 3(2x + 6) + 5 = 36x + 48
(24 + 30x) + 3(2x + 6) + 5 = 36x + 48

Reorder the terms:
24 + 30x + 3(6 + 2x) + 5 = 36x + 48
24 + 30x + (6 * 3 + 2x * 3) + 5 = 36x + 48
24 + 30x + (18 + 6x) + 5 = 36x + 48

Reorder the terms:
24 + 18 + 5 + 30x + 6x = 36x + 48

Combine like terms: 24 + 18 = 42
42 + 5 + 30x + 6x = 36x + 48

Combine like terms: 42 + 5 = 47
47 + 30x + 6x = 36x + 48

Combine like terms: 30x + 6x = 36x
47 + 36x = 36x + 48

Reorder the terms:
47 + 36x = 48 + 36x

Add '-36x' to each side of the equation.
47 + 36x + -36x = 48 + 36x + -36x

Combine like terms: 36x + -36x = 0
47 + 0 = 48 + 36x + -36x
47 = 48 + 36x + -36x

Combine like terms: 36x + -36x = 0
47 = 48 + 0
47 = 48

Solving
47 = 48

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -0.87y+2=y-0.6 | | -40=-8(8-m) | | -6(x-9)=-42 | | 7+8(4+4x)=6x-39 | | -8a+6a+42=1 | | 4x-3(x-1)=-4+3x+11 | | Fx=10x^2+8x+8 | | 22/2= | | 3x(x^2+2x-6)+4(x^2-6x+2)= | | g(x)=3.4x-8 | | 20n=10n^2 | | 2.2m=19.8 | | 13x+5=-35 | | 6=2(v+8)-4v | | 4(6y+1)+8=6(2y+5)-5 | | 0.9(5x+15)2.5-(x+3)= | | x^6+8y^3= | | (12y^3)+(24y^2)=3y+6 | | X+2x+(2x+30)=280 | | -x=4x-3 | | 4+3x-2=8x+18-3x | | -8=-8(2x-7) | | 93=(93)(63) | | st+3y=6 | | 8-3(1-3m)= | | 1.8+7n=9.5-4bn | | 0.60p+80=0.70+30 | | 2(6x-2)=3(5x-5) | | 6y^2+1y-2=0 | | Y=157.5x+50 | | 0.8y=-4 | | [-5/8][-8/15]= |

Equations solver categories